Pengaruh Bauran Ritel terhadap Keputusan Pembelian Konsumen pada Departemen Store X di DKI Jakarta - Freddy Simbolon (Binus Business Review, 2011)
This study aims to measure how much influence the retail mix to the purchasing decision. To measure, the study used 100 respondents to the Department Store buyer X. The analytical method used is multiple regression method. Based on the analysis results obtained under the seven aspects of the retail mix of Merchandising, Price, Location, Promotion, Store Design & Visual Product, Service, and Personnel, only two qualities that give them significant influence on consumer purchasing decisions of Price and Personnel. However, based on ANOVA, the overall of the seven aspects significantly influence consumer purchase decisions.